(untitled) (International Journal on Stereo & Immersive Media, 2025)
The principal application of the stereoscope is to induce apparent depth from two slightly different stimuli – usually photographs. In his classical article describing the stereoscope, Wheatstone referred to this as stereoscopic depth perception. Wheatstone also presented radically different patterns in the stereoscope thereby inducing binocular rivalry. Whereas stereoscopic depth perception reflects cooperation between the two eyes, binocular rivalry is evidence of their competition. Rivalry is an example of non-stereoscopic stereoscopy: the stereoscope is used to display a phenomenon that does not yield the perception of solidity. Anaglyphic examples are shown which indicate the scope of binocular rivalry art.